Stenting the arterial duct in neonates and infants with congenital heart disease and duct-dependent pulmonary blood flow: A multicenter experience of an evolving therapy over 18 years - Udink ten Cate, Floris E.A.; Sreeram, Narayanswami; Hamza, Hala; Agha, Hala; Rosenthal, Eric; Qureshi, Shakeel A. (Catheterization and cardiovascular interventions, 2013)
Objectives The primary aim of this multi‐institutional study was to describe our 18‐year experience of ductal stenting (DS) in infants with a duct‐dependent pulmonary circulation. The secondary aim sought to identify a subgroup of patients who may benefit the most using this evolving technique. Background No study has examined the extraordinary evolution of this promising therapy over the last two decades. Methods Between 1991 and 2009, 65 neonates and infants (39 male, 60%) underwent cardiac catheterization for DS in 3 participating centres. Patients were divided according to whether DS was attempted between 1991–2000 (Group 1, n = 20) or between 2001–2009 (Group 2, n = 45). Results DS was successful in 52/65 (80%) patients. DS outcome was associated with ductal morphology and cardiac diagnosis. DS failed more often in patients with univentricular physiology and tortuous duct morphology (p < 0.001). Most patients undergoing DS in Group 2 had pulmonary atresia with intact ventricular septum (PAIVS) (p < 0.001). DS was successful in 94% of these patients. Groups differed significantly in diameter and length of first implanted stent (p < 0.001), implanting additional stent (p < 0.001), and occurrence of complications (p = 0.033). Freedom from re‐intervention for the 52 patients was 92.3%. No procedure‐related mortality occurred. Conclusions The technical aspects and clinical application of percutaneous DS has changed in the last two decades. DS has become a practical and safe therapy in a subgroup of neonates with ductal‐dependent pulmonary blood flow.© 2013 Wiley Periodicals, Inc.